Female-headed households and their relationship with poverty in Latin America: a systematized review (Gestionar: revista de empresa y gobierno, 2022)
From a gender perspective, poverty is not a neutral condition, and it is recognized that female-headed households are more likely to live in poverty. The objective of this study was to investigate the causes that lead to female-headed households being at greater risk of living in poverty in Latin America. Method: a review of the literature of research published in the databases of: Scopus, Web of Science, Redalyc, Scielo, Dialnet and Latindex was carried out, combinations of terms and search equations were used with the variables "heads of family" and "poverty". Results: among the factors that explain the greater vulnerability of this social group, the demographic burden of households, disadvantageous conditions for entering the labor market, inequity in labor relations and lack of opportunities derived from gender stereotypes stand out. Conclusions: the study confirms that households headed by women are more exposed to living in poverty than those headed by men.
Keywords: família; família monoparental; mulheres; pobreza